2020 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
IFPRI’s 2020 Annual Report presents highlights from our research work around the world. Cutting-edge research on the impacts of the COVID-19 pandemic and related policies, and on our strategic research areas—climate resilience and sustainability, healthy diets and nutrition, inclusive and efficient food systems, institutions and governance, and rural transformation, as well as cross-cutting work on gender—is helping to inform policies and programs to end hunger and malnutrition.